2021
DOI: 10.1111/iar.12393
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb ages of zircons from metamorphic rocks in the upper sequence of the Hidaka Metamorphic Belt, Hokkaido, Japan: Identification of two metamorphic events and implications for regional tectonics

Abstract: The Hidaka Metamorphic Belt is a well-known example of island-arc crustal section, in which metamorphic grade increases westwards from unmetamorphosed sediment up to granulite facies. It is divided into lower (granulite to amphibolite facies) and upper (amphibolite to greenschist facies) metamorphic sequences. The metamorphic age of the belt was considered to be 55 Ma, based on Rb-Sr whole-rock isochron ages for granulites and related S-type tonalities. However, zircons from the granulites in the lower sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The Nakanogawa Group was metamorphosed to form the upper metamorphic sequence around 40-37 Ma (Kemp et al, 2007; Y. Takahashi et al, 2021). We speculate that another heat source must have existed at that time, but no obvious candidate has yet been identified.…”
Section: Origin Of the Hidaka Continental Crust Related To Ipr Subductionmentioning
confidence: 93%
“…The Nakanogawa Group was metamorphosed to form the upper metamorphic sequence around 40-37 Ma (Kemp et al, 2007; Y. Takahashi et al, 2021). We speculate that another heat source must have existed at that time, but no obvious candidate has yet been identified.…”
Section: Origin Of the Hidaka Continental Crust Related To Ipr Subductionmentioning
confidence: 93%
“…Protoliths of the metasediments are thought to have originated from the Nakanogawa Group in the east (Figure 1c), which has maximum depositional age of 66–48 Ma, and are suggested to have been deposited in a near‐trench setting close to the Eurasian continental margin during the Cretaceous–Eocene (Kimura, 1994; Nanayama et al, 2019). Metamorphic zircon ages reported for the granulites in the lower sequence include 39.6 ± 0.9 Ma for Crd‐Bt‐gneiss (Takahashi et al, 2021), 35.9 ± 0.9 Ma for Bt‐gneiss (Takahashi et al, 2021), 20.6 ± 1.0 Ma for Grt‐Opx‐Crd‐gneiss (Usuki et al, 2006) and 19.3 ± 0.3 Ma for Grt‐Opx‐gneiss (Kemp et al, 2007).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Maeda and Kagami (1996) suggested that the granulites were formed from accretionary wedge materials in a forearc setting in response to a thermal pulse triggered by subduction of the Izanagi–Pacific ridge during the late Palaeocene (c. 55 Ma). However, in more recent studies, zircon U–Pb dating from the HMB has yielded younger ages such as 39.6–32.5 Ma in pelitic granulites (Kemp et al, 2007; Ono, 2002; Takahashi et al, 2021) and 20.6–18.5 Ma in mafic granulites (Kemp et al, 2007; Kimura, 1996; Takahashi et al, 2021; Usuki et al, 2006). The difference in the age has led to confusion as to whether the HMB is a continuous sequence or a mosaic of different lithologic units that have undergone distinct metamorphic processes (Takahashi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations